Spatial analysis of zinc (Zn) heavy metal distribution in the waters of Staring Bay, Southeast Sulawesi - Wildayati; Armid; Takwir, Amadhan (Waste Handling and Environmental Monitoring, 2024)
Background: A spatial study of the distribution of heavy metal zinc (Zn) in the waters of Staring Bay, Southeast Sulawesi, has been conducted. This research aims to determine the spatial distribution of heavy metal Zn in the waters of Staring Bay. Methods: Sampling was carried out at 12 stations in the bay using a purposive sampling method. The concentration of heavy metal Zn in seawater samples was determined using an Atomic Absorption Spectrophotometer (AAS). Spatial analysis was performed using the Inverse Distance Weight (IDW) interpolation method (power = 2) with data processing software (ArcGIS 10.1). Findings: The results of the study indicate that the Zn metal concentration at the 12 research stations ranges from 0.0141 to 0.2085 ppm, with an average of 0.0668 ppm. The highest concentration of Zn metal is found at station 1. The results of the spatial analysis, with 12 stations, show that the area from the open sea to the coast of Tanjung Tiram Village has been contaminated with Zn heavy metal, ranging from 0.0132 to 0.2085 ppm. The same contamination is observed in the northern part of Wawosunggu Island, from the river mouth near Rumbia-rumbia Village to Lara Island, which has also been contaminated with a range of 0.0572 to 0.2085 ppm. Conclusion: Based on the contaminant factor (CF) values, the highest contamination by Zn metal occurs at station 1. Environmental variables (salinity, pH, temperature) show no significant effect on the concentration of Zn heavy metal. Novelty/Originality of this article: This study provides a comprehensive spatial analysis of zinc (Zn) contamination in Staring Bay, highlighting critical areas of pollution. It uniquely employs the Inverse Distance Weight interpolation method, revealing significant contamination patterns with minimal influence from environmental variables.